Kehidupan Masyarakat Etnis Tionghoa dan Arab Dalam Perspektif Sejarah Perdagangan di Kota Palembang - Agus Susilo; Yeni Asmara; Fitriyan Dela Widyaningrum (LP4MK STKIP PGRI Lubuklinggau, 2023)
The background in this research is about the history of the ethnic Chinese and Arabs in Palembang due to trade in the past that led to relations with the Malay community. The purpose of this study was to determine the life of the Chinese and Arab ethnic communities in the perspective of the history of trade in Palembang City. The method in this research is the historical research method. In this historical research method, there are steps that include: Heuristics (collection of sources) obtained from the results of journal and scientific book reviews, then criticism which consists of external criticism and internal criticism), the data that has been criticized is then adjusted to be suitable for use. in writing scientific articles, the last step is hirtoriography, namely writing history from the results of these sources into scientific writing. The results and discussion are the social life of the Chinese and Arab communities in Palembang, namely the Chinese and Arab communities in Palembang can develop well. Social interaction with the Malay community and other immigrant communities is well maintained. This good relationship creates cultural acculturation through marriage ties with the local community which gives birth to a new culture. Meanwhile, the relationship between the local community and the ethnic Chinese and Arab communities in Palembang was created because of good communication and both as social beings to need each other. Various sentiments against the Chinese and Arab communities over time can be avoided. People can live in peace and harmony by helping the prosperity of the city of Palembang as a city that maintains local history and traditions. The conclusion is that the Malay community can coexist with other ethnic groups that develop in the city of Palembang. This harmonious life is marked by cultural acculturation which adds to the uniqueness of the city of Palembang today.)